Effect of functional relaxation on the quality of life in patients with periprosthetic joint infection: Protocol for a randomised controlled trial. Issue 10 (17th October 2022) - Walter, Nike; Loew, Thomas; Alt, Volker; Rupp, Markus
Abstract : Introduction: Periprosthetic joint infection (PJI) is a devastating complication in orthopaedic and trauma surgery, which puts a high burden on the patients involving recurrent hospitalisation, prolonged courses of antibiotic medication, severe pain and long periods of immobility as well as high levels of psychological distress. Thus, this multicentre study aims at implementing body-oriented psychotherapy in clinical practice and evaluating its therapeutic effect on the quality of life. Methods and analysis: A prospective, parallel two-armed randomised controlled trial with approximately n=270 patients with verified PJI treated surgically with a one-staged exchange, or a two-staged exchange will be conducted. Functional relaxation (FR) therapy will be implemented as a group therapy. FR originally belongs to the psychodynamically based body-oriented psychotherapy. Intervention techniques consist of minute movements of small joints, which are performed during relaxed expiration accompanied by an exploration of differences of body feelings. A group will include 3–8 patients, led by a specialist physiotherapist certified in FR once a week. The participants are consecutively admitted to the class and participate in 12 sessions. The control group will consist of patients receiving an unspecific 'placebo relaxation' intervention for the same duration. The primary efficacy endpoint is the mental component summary and physical component summary of quality of life assessed by the 36-Item Short Form Health Survey (SF-36) after 6 months. Secondary outcomes include SF-36 scores after 12 months, consumption of pain medication, mobility measured by the Parker mobility score and the physical activity measured by daily steps with an accelerometer (actibelt). Ethics and dissemination: Approval from the Ethical Committee of the University Hospital Regensburg was received (file number: 21-2226-101). Written, informed consent to participate will be obtained from all participants. Results will be made available in the form of peer-reviewed publications and presentation in congresses. Trial registration number: DRKS00028881; German Clinical Trials Register.